The long road to regional cooperation - Rolf Hanisch (Intereconomics, 1978)
Cooperation measures conducive to increased integration between developing countries are considered to be necessary from the point of view of development theory as well as beneficial. Such measures are also in general welcomed, and on occasion even supported, by the governments of the industrialised countries. Organizations for the promotion of cooperation and integration of neighbouring countries have been brought into being in almost all regions of the Third World.
Keywords: 330; Asean